Penyuluhan Pencegahan Stunting dengan PMT Melalui Produk Olahan Puding Sayur dan Pembagian Tablet Tambah Darah di Desa Tulung, Saradan Madiun - Novi Ayuwardani; Sylvia Puspita; Rina Nurmaulawati; N Nurfitriawatie (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2024)
Improving the nutritional status of the community is an effort to reduce the prevalence of stunting in children under five years old, which is one of the priorities in the main targets of the 2020-2024 Medium-Term Development Plan. The utilization of local food is expected to be able to make the community independent in preventing stunting and not always depend on the government. There are many processed food products that can be used as additional food for additional child nutrition, one of which is pudding. Raw materials for making additional food can utilize vegetables and fruits. In this program we made pudding from spinach and pumpkin. Pumpkin has a fairly complete nutritional content such as protein, fiber, carbohydrates, Vitamin A, B and C. While spinach has many excellent benefits because it is a source of calcium, Vitamin A, Vitamin C, Vitamin E, fiber, beta-carotene, and has a very high iron content. This community service activity has been carried out starting from the planning, implementation and evaluation stages. From the results of this activity it can be concluded that the knowledge of the participants of this activity has increased about them about stunting in children and the importance of consuming blood supplement tablets.